Facile synthesis of high-quality Nano-size 10B-enriched fibers of hexagonal boron nitride - Ahmad, P.; Khandaker, Mayeen Uddin *; Rehman, F.; Muhammad, N.; Faruque, M. R. I.; Ullah, Z.; Khan, M. A. R.; Khan, G.; Khan, M. I.; Ali, H.; Haq, S.; Iqbal, Y.; et al. (MDPI, 2021)
The interesting properties of hexagonal boron nitride (h-BN) and its potential uses in thermo-structural advanced applications have been limited or restricted by its inherent brittleness, which can easily be eliminated by its fibers (h-BN) in nanoscale dimensions. The current study is based on the synthesis of nanoscale 10B-enriched fibers of h-BN (10BNNFs) from 10B in the precursors instead of B in two-hour annealing at 900 °C and one-hour growth at 1000 °C. All of the 10BNNFs are randomly curved and highly condensed or filled from 10h-BN species with no internal space or crack. XRD peaks reported the 10h-BN phase and highly crystalline nature of the synthesized 10BNNFs. 10h-BN phase and crystalline nature of 10BNNFs are confirmed from high-intensity peaks at 1392 (cm−1) in Raman and FTIR spectroscopes